Ice volume distribution and implications on runoff projections in a glacierized catchment - J. Gabbi; D. Farinotti; A. Bauder; H. Maurer (Hydrology and Earth System Sciences, 2012)
A dense network of helicopter-based ground-penetrating radar (GPR) measurements was used to determine the ice-thickness distribution in the Mauvoisin region. The comprehensive set of ice-thickness measurements was combined with an ice-thickness estimation approach for an accurate determination of the bedrock. A total ice volume of 3.69 ± 0.31 km3 and a maximum ice thickness of 290 m were found. The ice-thickness values were then employed as input for a combined glacio-hydrological model forced by most recent regional climate scenarios. This model provided glacier evolution and runoff projections for the period 2010–2100. Runoff projections of the measured initial ice volume distribution show an increase in annual runoff of 4% in the next two decades, followed by a persistent runoff decrease until 2100. Finally, we checked the influence of the ice-thickness distribution on runoff projections. Our analyses revealed that reliable estimates of the ice volume are essential for modelling future glacier and runoff evolution. Wrong estimations of the total ice volume might even lead to deviations of the predicted general runoff trend.